A Training Pelatihan Guru Anti Perundungan (Bulliying) di MTs Wihdatul Ulum Desa Bontokassi Kab. Gowa - Nengsi, Ratika; Syahid, Akhmad; Akidah, Ihramsari (Faculty of Tarbiyah and Teacher Training, 2024)
Bullying behavior is behavior that oppresses other people. Bullying has become a national and international issue, Indonesia itself has become one of the countries with a bullying emergency status. Bullies consider themselves to be individuals who are capable of doing anything to other people, especially if there is a difference of opinion or they feel unhappy with the person who is the victim of bullying. Whether intentionally or unintentionally, this bullying behavior is never justified. Regardless of place or age, bullying still occurs among students, with several factors causing it. The aim of this training is to provide understanding through training for teachers to become anti-bullying teachers through the Anti-Bullying Movement. The subjects in this community service are teachers at MTs. Wihdatul Ulum, Parangloe District, Gowa, is expected to become a pioneer in anti-bullying learning. The training will be provided in stages, the methods used are counseling and simulation which follows systematic planning, action, evaluation and reflection. The initial step is to observe the partner's situation, provide material for teacher introduction and understanding, then provide training on teacher strategies in learning to overcome bullying behavior. The problem faced by partners is the occurrence of bullying towards students outside and in the learning process. The lack of knowledge and understanding of teachers is certainly one of the causes, as well as students' overall activities that cannot be controlled. Students who experience bullying are dominated by non-verbal bullying (body shaming). Through this training, sanctions and resolution and prevention efforts have been created to eliminate bullying in educational institutions and in the community.